Intellectual Property as one of the Major Tendencies of Innovative Development of Railway Transport - TÑ–manjuk, Valeria; Chernenko, Yuliya (International Journal of Engineering and Technology, 2018)
The paper deals with the issues of effective formation and use of intellectual property in the transport system with the example of a public joint-stock company â€œUkrainian Railwaysâ€ (UR). Within the framework of the reorganization of the UR structure it is proposed to create an â€œIntellectual Property Management Officeâ€, which forces are aimed at attracting the best scientific protectable designs and innovation projects, created both on the basis of their own enterprise and subject universities and organizations; the justification concerning the necessity of preparation of the patent policy is provided, which should correspond to the innovation strategy of the enterprise development; the economic-mathematical model is proposed, which allows to reach the optimum implementation of works that must be performed in accordance with the UR patent policy; the calculations of possible economic effects due to the commercialization of intellectual property objects are presented. It is substantiated that the use of intellectual property by the UR will enhance its image, competitiveness, become one of the tools of investment attraction, and will result in receiving additional profit.Â Â
Keywords: Economic effect; intellectual property management system; intellectual property; objects of intellectual property; OIP Commercialization; patent policy.